1997
DOI: 10.1038/sj.leu.2400841
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of minimal residual disease in adult and childhood acute lymphoblastic leukaemia reveals differences in treatment response

Abstract: Immunoglobulin heavy chain gene (IgH gene) rearrangementsburden between 10 4 and 10 5 cells. 16,17 Similarly, although are found in the majority of patients with B lineage acute lym-PCR positivity often precedes clinical relapse, [7][8][9][13][14][15] bone marrow in cohorts of childhood, and adult ALL patients. groups. However, the proportion of positive tests dropped below 15% at a later stage in adults (4-6 months) than in chil-Similarly, end of treatment MRD assessment has been pro- dren (2-3 months). Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 2 publications
(2 reference statements)
4
38
0
1
Order By: Relevance
“…2,3,5,6 The so-called real-time quantitative PCR (RQ-PCR) techniques offer the possibility for rapid and reproducible quantitation of MRD levels without post-PCR handling, thereby preventing contamination with PCR products. 133,192,193 The molecular laboratories of the BIOMED-1 Concerted Action have therefore now initiated a large study group of 25 laboratories from 10 European countries in order to standardize the RQ-PCR analyses of chromosome aberrations using the TaqMan technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,6 The so-called real-time quantitative PCR (RQ-PCR) techniques offer the possibility for rapid and reproducible quantitation of MRD levels without post-PCR handling, thereby preventing contamination with PCR products. 133,192,193 The molecular laboratories of the BIOMED-1 Concerted Action have therefore now initiated a large study group of 25 laboratories from 10 European countries in order to standardize the RQ-PCR analyses of chromosome aberrations using the TaqMan technique.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular the (semi-) quantitative measurement of the decrease of the leukemic cell load during the first phases of treatment has high prognostic value. In childhood acute lymphoblastic leukemia (ALL) this application of MRD measurement has been proven to identify an unprecedented large group of low-risk patients (40-45%) with a 4-year relapse rate of only 2%, and a high-risk group (15%) with a 4-year relapse rate of 80%.…”
Section: Prefacementioning
confidence: 99%
“…With this approach, a detection limit of 5 × 10 −5 was reached in five cases and of 10 −3 in one case, which may not be sensitive enough for clinical application in ALL. 1,5,6,28,29 This problem has also been described in a recent paper by Pongers-Willemse et al, 13 who showed that this type of RQ PCR appeared to be comparable to quantification by dot-blotting but less sensitive than liquid hybridization. An additional disadvantage of this procedure is the expensive and time-consuming need for unique primer and probe sets for each individual patient.…”
Section: Design Of Primers and Probes For Rq Pcrmentioning
confidence: 87%
“…14,17,35 In precursor-B-ALL, this especially concerns junctional regions of IGH, IGK, TCRG and TCRD genes. 15 For this purpose the precise configuration of the gene rearrangements (ie the V(D), and J gene segments) has to be identified at diagnosis.…”
Section: Figurementioning
confidence: 99%